JIHAD DAN TERORISME DALAM PANDANGAN HUKUM ISLAM (Sebuah Analitis Kritis Terhadap Skenario Politik Global) - Sudianto Sudianto (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri Bone, 2018)
Jihad is to mobilize all abilities to achieve goals with no surrender and despair, so in this case jihad is not only against the enemy but if there is a leader of the fight against unemployment, poverty, eradicate immoral pursuit of pleasure of Allah and for the welfare of its people then this could also referred to as jihad. While terrorism is any act of political violence that has no moral and legal justification, whether it is an act of violent revolutionary group or government / state. Terrorism has two categories, first is the horrific terrorism, that terrorism is truly evil because it destroys private property and state and kill people without reason that rational and unconventional manner. Second, heroic terrorism, namely acts of terrorism to fight for life, such as suicide bombings carried out Palestinian youth. Actions taken as lacking any other choice. So the first category is condemned by Islam because it has been killing innocent people, even the perpetrators can be subject to capital punishment. While the second category is a form of holy struggle that when the fighters are dead they are called martyrs for defending the truth and want to obtain their rights which are usurped by the Zionist state.